1969
DOI: 10.1084/jem.130.4.765
|View full text |Cite
|
Sign up to set email alerts
|

Immunocompetence of Spleen Cells From Neonatally Thymectomized Mice Conferred in Vitro by a Syngeneic Thymus Extract

Abstract: Impaired immunological competence of spleen cells from neonatally thymectomized C57B1/6 young adult mice was apparent when these cells were tested in an in vitro graft-versus-host assay. Spleen cell inocula prepared from thymectomized mice did not induce enlargement of (C3H/eb x C57BI/6)F1 newborn spleen explants, whereas the same number of cells from intact donors consistently initiated splenomegaly. Spleen enlargement was observed, however, when the explants were challenged by cells from thymectomized donors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

1973
1973
1978
1978

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 33 publications
1
40
0
Order By: Relevance
“…We found previously that immunological impairment of the host as a result of neonatal thymectomy (Trainin et at., 1967), or ALS treatment (Trainin and Linker-Israeli, 1970) was associated with an increase in the yield of lung adenomata.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found previously that immunological impairment of the host as a result of neonatal thymectomy (Trainin et at., 1967), or ALS treatment (Trainin and Linker-Israeli, 1970) was associated with an increase in the yield of lung adenomata.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported previously that an impairment of thymus function was followed by a higher carcinogenic response to urethane in mice (Trainin et al, 1967;Trainin and Linker-Israeli, 1970). The effects of the injection of autosensitized lymphocytes upon the T cell competence of the recipients in our experiments was examined.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The extract from syngeneic or allogeneic mice restored the ability of thymectomized mice to reject skin grafts . Trainin et al (1969) (Robey, 1973). Thymosin was found to accelerate the development of immunocompetence in spleen cells in normal, neonatal mice after injection of the extract on days 1 and 2 after birth.…”
Section: Action Of Thymic Extracts On the Immune Responsementioning
confidence: 99%
“…Cohen et al (40) reported that the addition of thymosin to one-way MLCs resulted in an increase in the proliferative response of thymus cells but a decrease in the response of spleen cells to alloantigen. Another thymus product, thymus humoral factor, is also assumed to be a product of the reticuloepithelial cells of the thymic medulla, although its cellular origin is less well-defined than in the case of the factors discussed above (41)(42)(43). Thymus humoral factor has been observed to either increase or decrease MLC reactivity, depending upon the assay conditions utilized.…”
mentioning
confidence: 99%